Combining patient talk about internet use during primary care consultations with retrospective accounts. A qualitative analysis of interactional and interview data. (March 2021) - Stevenson, Fiona A.; Seguin, Maureen; Leydon-Hudson, Geraldine; Barnes, Rebecca; Ziebland, Sue; Pope, Catherine; Murray, Elizabeth; Atherton, Helen
Abstract: Despite widespread acknowledgement of internet use for information about health, patients report not disclosing use of online health information in consultations. This paper compares patients' reported use of the internet with matched video recordings of consultations. The concepts of doctorability and epistemics are employed to consider similarities and differences between patients' reports in interviews and actions in the consultation. Data are drawn from the Harnessing Resources from the Internet study conducted in the UK. The data set consists of 281 video-recorded general practice consultations, with pre-consultation questionnaires completed by all patients, interviews with all 10 participating doctors and 28 selected patients. We focus on the 28 patient interviews and associated consultation recordings. A conversation analytic (CA) approach is used to systematically inspect both the interview and consultation data. In interviews patients presented use of the internet as associated with appropriate self-management and help-seeking. In consultations patients skilfully translated what they had found on the internet in order to provide grounds for the actions they sought. We conclude that patients translate and utilise what they have found on the internet to assert the doctorability of their presenting problems. Furthermore, patients design their talk in both interviews and consultations to accord with their understanding of the epistemic rights of both doctors and patients. Patients search the internet so they are informed about their medical problem, however they carefully manage disclosure of information to avoid disrupting the smooth running of medical interactions. Highlights: Patients seek information from the internet to support decisions to consult. Patients seek information from the internet to support appropriate self-management. Patients skilfully translate what they find on the internet to support requests. Patients skilfully use the internet to invite action from their doctors. Patients do not openly challenge the epistemic authority of the doctor.